Adoption of OS6 Variety of Rice in Ife Division, Oyo State of Nigeria - Jibowo, A. A. (Faculty of Agriculture, University of Ife, 2015)
An investigation was conducted into the factors that influenced the adoption of the OS6 variety of rice in Ife Division. The extent and rate of adoption of the crop, the problems, personal and socio-economic characteristics of the rice farmers and farm characteristics associated with adoption of the crop were studied. Fifty-four adopters and 56 randomly selected non-adopters were interviewed in 8 villages where the crop had been adopted, between September and December, 1975. Data analysis showed a four-year time-lag between awareness and adoption of the crop. Statistically significant associations were found between age, years of schooling, innovation proneness, family labour, income, use of mass media, access to credit facilities, participation in organisations, cosmopoliteness, knowledge of extension workers, method of acquiring farmland, farm size, discontinuance of planting some crops, growing of permanent of annual crops, and adoption. No significant relationship was found between farming experience and adoption. Invasion by field pests was the major problem encountered.